Preferensi Politik Pengikut Tarekat Qadiriyah Di Majene Dalam Pemilukada Kabupaten Majene Tahun 2011 - Arsyad, Amin (Jurnal Adabiyah, 2014)
The solidness of âtarekatâ followers political preference which tends to show their obedience to their teacher in making political choice has made âtarekatâ groups often taken as a base of political support by competing candidatesÂ  in politica contest, so happens on the âtarekat Qadiriyahâ in Majene election 2011. This research is aimed to analyze the political preference formation of âtarekat Qadiriyahâ Majene and the reason of their obedience to their teacherâs political will. The research location is âKabupaten Majeneâ, West Celebes Province. The research base used is qualitative research with descriptive research analysis. Informer picking technique used is the purposive technique, so the âtarekat Qadiriyahâ teacher, group leader, follower, politicians who follow the âtarekat Qadiriyahâ is made as informers in this research. Data collection technique is in depth interview, observation, and literature study with qualitative data analysis technique. The âtarekat Qadiriyahâ political preference formation in Majene is caused by their relatively opened paradigm to see the connection between religion and politics. That view caused the assumption that the âtarekatâ group involvement in politics is a good thing if aimed for something good. The formation of âtarekat Qadiriyahâ teacherâs political view in Majene as the political choice maker of the âtarekatâ group he leads is based on his interpersonal relationship with the political actor and the judgement on the actorâs performance in supporting the development of the âtarekatâ lesson he leads.